2015
DOI: 10.1007/s11695-015-1979-x
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacotherapy in Conjunction with a Diet and Exercise Program for the Treatment of Weight Recidivism or Weight Loss Plateau Post-bariatric Surgery: a Retrospective Review

Abstract: Phentermine and phentermine-topirimate in addition to diet and exercise appear to be viable options for weight loss in post-RYGB and LAGB patients who experience WR or WLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 20 publications
8
58
1
Order By: Relevance
“…The mean of this added weight loss was −7.6% (17.8 lbs) of total postsurgical weight. After further stratification, we found that patients who were prescribed medication at weight plateau lost a similar amount of weight compared to those who were prescribed medication after weight regain, (− 6.9% or 16.1 lbs and − 7.7% or 18.2 lbs) consistent with findings reported in previous literature [27,28,32,33]. Consequently, total weight loss percentage from preoperative status was higher in patients who were prescribed medications at their plateau than in those patients who were prescribed medication after weight regain had occurred (32.3% versus 26.8%; P = .486).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The mean of this added weight loss was −7.6% (17.8 lbs) of total postsurgical weight. After further stratification, we found that patients who were prescribed medication at weight plateau lost a similar amount of weight compared to those who were prescribed medication after weight regain, (− 6.9% or 16.1 lbs and − 7.7% or 18.2 lbs) consistent with findings reported in previous literature [27,28,32,33]. Consequently, total weight loss percentage from preoperative status was higher in patients who were prescribed medications at their plateau than in those patients who were prescribed medication after weight regain had occurred (32.3% versus 26.8%; P = .486).…”
Section: Discussionsupporting
confidence: 89%
“…To date, there is a paucity of published literature on utilizing weight loss medication as an adjunct to bariatric surgery for individuals who have had inadequate weight loss or for individuals who have regained weight after undergoing bariatric surgery. We are aware of only a few studies that have examined this issue [27,28,32,33]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribing weight loss pharmacotherapy before weight regain occurs (at weight plateau) may result in greater amount of total weight loss from the pre-operative period [159] and may prevent weight regain. A recent retrospective review demonstrated that phentermine alone and a phentermine-topiramate combination, in addition to diet and exercise, appear to be viable options for weight loss in RYGB and adjustable gastric banding patients who experienced weight recidivism or weight loss plateau [160]. Another study showed that medical treatment directed to the control of satiety using liraglutide may be an alternative treatment of patients with poor weight loss or weight regain after surgery [161].…”
Section: Weight Regain Prevention and Managementmentioning
confidence: 99%